1984
DOI: 10.3382/ps.0630354
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Phosphorus at 0, 6, and 21 Hours Postoviposition in Hens Laying in the Morning or Afternoon

Abstract: Two experiments were conducted using White Leghorn hens. Blood samples were collected immediately following oviposition (0 hr) or 6 or 21 hr postoviposition from hens laying in the morning or afternoon. Plasma phosphorus was determined at each time period. In Experiment 1, plasma phosphorus at oviposition was essentially the same for hens laying in the morning or afternoon (3.95 and 4.10 mg/dl, respectively). At 6 hr postoviposition plasma phosphorus was lower than that observed at 0 hr (3.22 and 3.15 mg/dl, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

1985
1985
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
1
6
0
5
Order By: Relevance
“…Also, for any given level of P, when hens were fed diets low in Ca, feed intake was depressed (Roush et al, 1986). This decrease in feed intake may also be related to the elevated concentrations of P in plasma reported by Miles et al (1984). Although plasma P was not measured, apparent P retention (Table 3) indicates that hens fed 2.5% Ca retained less grams total P on SF days compared tained.…”
Section: Resultsmentioning
confidence: 70%
“…Also, for any given level of P, when hens were fed diets low in Ca, feed intake was depressed (Roush et al, 1986). This decrease in feed intake may also be related to the elevated concentrations of P in plasma reported by Miles et al (1984). Although plasma P was not measured, apparent P retention (Table 3) indicates that hens fed 2.5% Ca retained less grams total P on SF days compared tained.…”
Section: Resultsmentioning
confidence: 70%
“…93, 6.17, 6.79 mg/dl; P = 0.0811; Table 4. Miles et al (1984), after performing experiments, reported that the average of P content in plasma at the time of oviposition for hens fed in the morning or afternoon was 3.95 and 4.10 mg/dl, respectively. On the other hand, higher values from 4.91 to 5.90 mg/dl were obtained from the plasma of hens which blood was collected 21 h after oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…The hens were marked with dye and 21 h after oviposition, blood samples were collected once again (Miles et al, 1984;Junqueira et al, 2002). Blood samples from each treatment were placed in tubes and packed in ice.…”
Section: Analysis Of Calcium and Phosphorus Level In Bloodmentioning
confidence: 99%
“…The thicker shells of HS eggs collected at 0700 vs. 1100 hr appear to be related to increased shell phos-phorus rather than shell calcium, magnesium, or manganese content. The decrease in plasma phosphorus observed in hens laying afternoon eggs as compared to morning eggs (Miles et al, 1984) may be due to increased transport of phosphorus from the blood to the shell gland, thus explaining the higher shell phosphorus content of HS eggs collected at 0700 hr as compared to those collected at 1100 hr.…”
Section: Egg Productionmentioning
confidence: 82%